1989
DOI: 10.1101/gad.3.10.1553
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian pre-mRNA branch site selection by U2 snRNP involves base pairing.

Abstract: SV40 early pre-mRNA is alternatively spliced to produce large T and small t mRNAs by use of different 5'-splice sites and a shared 3'-splice site. The large T splicing pathway uses multiple lariat branch sites, whereas small t splicing, constrained by its small intron size, can use only one. We exploited this situation to test the hypothesis that RNA-RNA base pairing between U2 snRNA and the branch site sequence is important in mammalian pre-mRNA splicing by constructing and analyzing several mutations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
254
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(263 citation statements)
references
References 55 publications
9
254
0
Order By: Relevance
“…In spite of the documented conservation of c35 and its apparent role in branch-site structure (these studies), functional studies have not found that this specific modification is essential for splicing+ Mutational studies of the U2 snRNA-intron pairing by Wu and Manley (1989) demonstrated that branch-site selection involves the base pairing of U2 snRNA to a consensus sequence of the intron+ These authors found, however, that other base pairs can substitute for the wild type, albeit not as efficiently+ Another study by Yu and colleagues (1998) found that the modifications in the first 27 nt of Xenopus U2 snRNA were the only sites critical for snRNP assembly, likely because they mediate the specificity of RNA-protein interactions; nine U2-specific proteins are known to bind with low affinity the first stem-loop of free U2-snRNA (Behrens et al+, 1993)+…”
Section: Conservation Of C35mentioning
confidence: 97%
See 2 more Smart Citations
“…In spite of the documented conservation of c35 and its apparent role in branch-site structure (these studies), functional studies have not found that this specific modification is essential for splicing+ Mutational studies of the U2 snRNA-intron pairing by Wu and Manley (1989) demonstrated that branch-site selection involves the base pairing of U2 snRNA to a consensus sequence of the intron+ These authors found, however, that other base pairs can substitute for the wild type, albeit not as efficiently+ Another study by Yu and colleagues (1998) found that the modifications in the first 27 nt of Xenopus U2 snRNA were the only sites critical for snRNP assembly, likely because they mediate the specificity of RNA-protein interactions; nine U2-specific proteins are known to bind with low affinity the first stem-loop of free U2-snRNA (Behrens et al+, 1993)+…”
Section: Conservation Of C35mentioning
confidence: 97%
“…The branch-site consensus sequence is poorly conserved among eukaryotes (Wu & Manley, 1989)+ In group II introns, not only are the base pairs flanking the bulged adenosine poorly conserved among these selfsplicing introns, but the first step of splicing apparently occurs if the branch-site adenosine is involved in a Watson-Crick base pair (Chu et al+, 1998)+ This finding may diminish the importance of a pseudouridine residue in the spliceosome that facilitates bulging of this residue+ However, there are many documented differences between branch-site recognition in group II introns and spliceosomes+ Specifically, the N6 of the branch-site adenosine is the major determinant in recognition in group II introns (Liu et al+, 1997) whereas the N1 is the most important substituent in spliceosomes (Query et al+, 1996)+ Also, a cytosine can be tolerated at the spliceosome branch site, but it is not acceptable as a branch point in group II introns+ These differences suggest a different mode of recognition for the branch site in spliceosomes and group II introns+…”
Section: Conservation Of C35mentioning
confidence: 99%
See 1 more Smart Citation
“…The spliceosome assembles de novo on each premRNA molecule, and distinct intermediates in the assembly pathway can be observed in vitro+ The first binding events form the commitment or early complex (CC or E) and are ATP independent+ In this complex, the 59 splice site is recognized by U1 snRNP and mammalian proteins SF1 and U2AF 65 , or yeast proteins BBP and MUD2, bind the branch region and pyrimidine tract, respectively+ In the mammalian system, recent evidence suggests that U2 snRNP is loosely associated at this time, but not yet stably engaged (Das et al+, 2000), although such an association has not been detected in yeast (Liao et al+, 1992)+ In both mammals and yeast, the first ATP-dependent step is the stable binding of U2 snRNP to the pre-mRNA branch site (Cheng & Abelson, 1987;Konarska & Sharp, 1987;Krämer, 1988;Pruzan et al+, 1990;Michaud & Reed, 1991;Liao et al+, 1992), in part, through U2 snRNA•branch region base pairing (Parker et al+, 1987;Wu & Manley, 1989;Zhuang & Weiner, 1989)+ This forms complex A in the mammalian system+ Subsequently, a larger complex, B, is formed by association of U4/U5/U6 tri-snRNP+ Complex C follows B after significant rearrangements and is the active spliceosome, containing U2/5/6 snRNPs and splicing intermediates (reviewed in Moore et al+, 1993)+ In the mammalian system, both the mechanistic basis for the ATP requirement during U2 snRNP addition and the factor(s) utilizing the ATP remain unclear+ U2 snRNP is a 17S complex composed of U2 snRNA and approximately 20 proteins that form ordered subdomains (Krämer et al+, 1999;reviewed in Will & Lührmann, 1997)+ A major U2 protein component, SF3, composed of two heteromeric complexes SF3a and SF3b, has been implicated in stabilization of the U2 particle via contact to the RNA 59 to the branch region (also called the anchoring region; Gozani et al+, 1996)+ One SF3b protein, SF3b-155, additionally contacts the RNA on the 39 side of the branch region (Gozani et al+, 1998), and another SF3b-associated protein, U2-p14, contacts RNA within the branch region )+ In both yeast and mammals, SF3 can dissociate from U2 snRNP in vitro, indicating that a remodeling of the particle may be important for its function (Krämer, 1996;Pauling et al+, 2000)+ Other factors, including U2AF 35 and SR proteins, also contribute to stable U2 snRNP binding+ Yeast U2 addition also requires the presence of two DExH/D ATPases (Prp5p and Sub2p), but their targets are not yet known (Ruby et al+, 1993;Kistler & Guthrie, 2001;Libri et al+, 2001;Z...…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, branching occurs within an almost invariant sequence, U Ϫ5 A Ϫ4 C Ϫ3 U Ϫ2 A Ϫ1 A 0 C ϩ1 (the branch A is underlined and the surrounding nucleotides are numbered relative to the BP nucleotide), 20-30 nt upstream from the 39 splice site (Burge et al+, 1999;Lopez & Séraphin, 1999)+ The mammalian BP sequence is less well conserved but generally conforms to the consensus Y Ϫ5 N Ϫ4 Y Ϫ3 U Ϫ2 R Ϫ1 A 0 Y ϩ1 (Y ϭ pyrimidine, R ϭ purine, N ϭ any nucleotide; Keller & Noon, 1984;Reed & Maniatis, 1988;Green, 1991) and the yeast BP consensus sequence is believed to be the most optimal BP sequence also in mammalian cells )+ Recognition of the BP sequence and definition of the branched nucleotide is mediated by base pairing of an invariable sequence in the U2 snRNA (Nelson & Green, 1989;Wu & Manley, 1989;)+ It has been suggested that the BP nucleotide is bulged out from this RNA duplex and that this may activate the 29 hydroxyl group for nucleophilic attack (Query et al+, 1994)+ The natural BP nucleotide is highly conserved as an adenosine and only a few natural examples of branching to other nucleotides are known+ For example, branching of the first intron of the human growth hormone gene and the third intron of the human calsitonin/CGRP gene occur mainly at a cytosine and a uridine, respectively (Adema et al+, 1988;Hartmuth & Barta, 1988); the second intron of the human immunodeficiency virus type 1 (HIV-1) tat /rev intron pre-mRNA branches frequently at a uridine residue (Dyhr-Mikkelsen & Kjems, 1995); and branching to a guanosine residue was reported for the minor latency associated transcript (mLAT) from the herpes simplex virus type 1 (HSV-1) (Zabolotny et al+, 1997)+ Because the efficiency of the first step of splicing is reduced considerably when nonadenosine acceptors are used (Query et al+, 1996), these systems may represent examples of important regulatory elements of splicing+ Given the degeneracy of BP sequences in higher eukaryotes and the fact that potential BP sequences are nearly randomly distributed in introns and exons (Harris & Senapathy, 1990), the BP sequence must act in cooperation with other elements+ The 39 boundary of an intron is also defined by sequences between the BP sequence and the 39 splice site+ In a survey of higher eukaryotic introns, the branch sites were mapped 18-37 nt upstream from the highly conserved AG dinucleotide at the 39 splice site separated by a polypyrimidine tract of variable length (Green, 1991)+ The polypyrimidine tract is important for complex E formation in initial steps of the spliceosome assembly (Freyer et al+, 1989), but the sequence requirement appears to be quite flexible in higher eukaryotes+ Important parameters for the strength of a polypyrimidine tract are leng...…”
Section: Introductionmentioning
confidence: 99%